Research and Prospect Analysis of Sports Consumption Willingness Based on Public Health Emergencies - Liu, Ziyuan; Guo, Rui; Liu, Jia; Dong, Fan; Shi, Yang; Cai, Qi (Frontiers in Psychology, 2022)
In 2020, the sudden outbreak of coronavirus has had a great impact on the health and life of people all over the world, and the sports industry is facing unprecedented challenges because of its participation and strong clustering. On the basis of questionnaire survey, literature analysis and other research methods, this paper introducethes SOR theory and takes Kunshan citizens' sports and consumption as the research subject, and draws lessons from structural equation model (SEM) to build a theoretical model of sports consumption characteristics and future consumption willingness. The results of empirical analysis show that: Physical sports consumption has been greatly affected by the epidemic, but because people realize the importance of sports, residents' willingness to consume sports increases, and the venue and other factors affect the ornamental and participating sports consumption willingness decreases.At the same time, the restrictive factors, such as lower educational back-ground, increased age and lack of time, make the sports consumption willingness of this charac-teristic group significantly lower than that of other citizens. This paper puts forward some suggestions for relevant government departments to im-prove citizens' sports consumption willingness. In order to expand the development prospect of sports industry from a long-term perspective, it can provide reference for the development of sports consumption.